Generation of a KDM5D knockout human embryonic stem cell line with CRISPR/Cas9 technology - Ouhui Li; Yuting Zhen; Chao Sun; Yanlin Ma; Qi Li; Luan Wen (Stem Cell Research)
KDM5D is a gene implicated in spermatogenic failure and sex-related differences in colon cancer progression, though its role in spermatogenesis remains unclear. We successfully generated a KDM5D knockout human embryonic stem cells using CRISPR/Cas9 technology. This knockout cell line provides a valuable model for studying KDM5D’s function in spermatogenesis and its influence on sex differences in various diseases.